Issues concerning relations between business and society in teaching Business History in the United States and Poland - Jastrząb, Mariusz (Annales. Etyka w Życiu Gospodarczym, 2019)
Based on empirical material in the form of case studies prepared at Harvard Business School and Kozminski University, the article analyses the content of teaching materials in the field of business history. The Harvard case studies served as a model for the Polish ones. In contrast to the United States, at Kozminski University and in other Polish business schools, business history is not taught as a separate subject. The article puts forward the thesis that history education could provide an opportunity for future managers to broaden their knowledge of the social environment in which they will operate and to shape attitudes of responsibility for the social consequences of decisions made. However, this opportunity remains largely untapped in both the United States and Poland. American teaching materials are still influenced by the Chandlerian paradigm, and therefore they focus on the evolution of structures and changes in the strategy of large multinational corporations. These materials present students with role models of successful entrepreneurs and companies. Their social environment is presented in a sketchy manner, and questions about the motivations of human actions or hierarchies of values are rarely asked. The teaching materials also shy away from questions about the social consequences of managerial decisions. This is so, despite the fact that scientific publications are moving away from concentrating solely on the centre of global capitalism, the history of the largest corporations, and the treatment of the social environment as a variable on which the entrepreneur or company have no influence. Business history as a scientific discipline in Poland is still at an early stage of development. However, one can notice a gap between research and teaching similar to the one that exists in the USA: there are works critically analysing the period of transformation and showing the peripheral character of Polish capitalism as well as the social consequences of this peripheral nature that are completely ignored in teaching.